Influence of GABA-producing yeasts on cheese quality, GABA content, and the volatilome. (15th January 2022) - Li, Yandie; Wang, Tong; Li, Shan; Yin, Pingping; Sheng, Huayang; Wang, Tengbing; Zhang, Yan; Zhang, Kaili; Wang, Qingling; Lu, Shiling; Dong, Juan; Li, Baokun
Abstract: To explore the influence of γ-Aminobutyric acid (GABA)-producing yeast on the quality of cheese, Pichia kudriavzevii 1–21, Kluyveromyces marxianus B13-5, Saccharomyces cerevisiae DL6-20, Kluyveromyces lactis DY1-10, and a commercial starter were used to make cheese, with only the commercial starter used as a control. The results showed that K. marxianus B13-5 produced cheese had the highest GABA content (up to 489 mg/kg) and a relatively good texture, and K. lactis DY1-10 increased the production of amino acids. Principal component analysis and orthogonal partial least squares discrimination analysis were performed to distinguish the different substances in the yeast-produced cheeses from those of the control cheese. Headspace solid phase microextraction-gas chromatography-mass spectrometry of aroma compounds demonstrated that the four cheeses had strong fruity, apple, and pineapple aromas, and the yeasts all produced butanoic acid, ethyl ester, acetic acid ethyl ester, hexanoic acid, ethyl ester, and octanoic acid, ethyl ester. Compared with the control group, the different substances in the yeast-produced cheeses were 2-heptanol, 1-propanol, 2-methyl-, benzene ethanol, isoamyl alcohol; propanoic acid, 2-methyl-, acetic acid; 2-butanone; 3-hydroxy-, octanoic acid ethyl ester, and acetic acid ethyl ester. Cheese made by GABA-producing yeast could have potential probiotic effects and improved flavor. Highlights: The effects of yeast-produced GABA on cheese characteristics were studied. All four yeast affected the texture and aroma properties of the cheeses. The yeast-produced cheeses had strong fruity, apple and pineapple aromas. The control and yeast -produced cheeses contained different volatile compounds. GABA-producing yeast have potential probiotic effects and improve cheese flavor.